The correlations among detonation velocity, heat of combustion, thermal stability and decomposition kinetics of nitric esters - Gong, Jun; Yan, Qi Long; Liu, Pei Lin; He, Wei; Qi, Xiao Fei; Zeman, Svatopluk (Springer, 2018)
In this paper, the thermal stability and decompn. kinetics of 10 nitric esters including nitroglycerin (NG), pentaerythritol tetranitrate (PETN), trimethylolethane trinitrate (TMETN), dipentaerythritol hexanitrate (DiPEHN), trimethylolpropane trinitrate (TMPTN), xylitol pentanitrate (XPN), sorbitol hexanitrate (SHN), erythritol tetranitrate (ENT), mannitol hexanitrate (MHN) and nitroisobutylglycerol trinitrate (NiBGT) are investigated by non-isothermal TG and DSC. It has been shown that the mass loss processes of NG, TMETN and TMPTN are more dependent on the heating rate, and the simultaneous evapn. makes the initial temps. for their mass loss lower than those of the other nitric esters. Based on the correlations among their thermal stability, activation energy, detonation velocity and heat of combustion, one could conclude that the oxygen coeff. (a) plays a pos. role on the decompn. heat release efficiency (hd) when it is less than one, whereas when the a is greater than or equals to one, the fuel elements such as C and H contents would play a decisive role on hd. It has been further proved that the order of contribution rate of function groups on the tertiary carbon to the detonation velocity could be -CH3 < -NO2 < -C2H5 < -ONO2. In addn., the introduction of function groups to the tertiary carbon is in favor of increasing the thermal stability of nitric esters due to increase in symmetry and rigidity of their mols. The proportion nos. (Cs) of methylene group (-CH2-) to tertiary carbon or quaternary carbon will, to some extent, det. the thermal stability of the nitric esters.
Vztah mezi detonační rychlostí, spalným teplem, tepelnou stabilitou a rozkladnou kinetikou dusičných esterů.
Keywords: Nitric esters; Thermal stability; Heat of combustion; Critical temperature; Oxygen balance; Dusičné estery; Tepelná stabilita; Spalné teplo; Kritická teplota; kyslíková bilance